Mandatory IFRS adoption: the trade-off between accrual-based and real earnings management/Elisabetta Ipino, Antonio Parbonetti - Ipino,Elisabetta.
This paper examines whether firms substituted real earnings management for accrual-based earnings management after the International Financial Reporting Standards (IFRS) became mandatory. Using a sample of 101,331 firm-year observations from 33 countries between 2000 and 2010, we show that IFRS adoption came with the unintended consequence of certain firms substituting real earnings management for accrual-based earnings management, especially among firms in countries with strict enforcement regimes. Furthermore, we document that the trade-off is confined to EU countries in which strong firm-level characteristics (i.e. the firm-level mechanism of control, the market’s level of scrutiny, and firm-specific incentives to provide transparency) are coupled with strong enforcement. We also show that IFRS had an effect in countries outside the EU, albeit at a different time. Overall, the results suggest that accounting regulators’ efforts to increase earnings quality might have had the unintended consequence of increasing real earnings management activities.